Accurate Reduction of Sea Level Records - Graff, Jerzy; Karunaratne, Anil (The International Hydrographic Review, 2015)
The established procedures for the reduction of tide gauge sea level records have been critically reviewed and adapted for systematic processing. Various new methods have been developed for screening and verification of digitised sea level data and a computer-based system has been developed to process and archive these data in a uniform fashion. The system, intended for the routine processing of the class A network of tide gauges around the British Isles, presents a new level of standards in the processing of coastal sea level records.